PENERAPAN SIMULASI PHET DENGAN MODEL PROBLEM-SOLVING UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VIII SMP MATERI CAHAYA - Rahyu Darsiyana; Azizahwati; Ernidawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Teachers often face challenges when introducing new concepts that students are unfamiliar with, and students are rarely accustomed to connecting prior knowledge to construct new concepts. These teacher-related barriers and student difficulties contribute to low conceptual understanding. To address this, innovative learning strategies such as the application of PhET simulations combined with problem-solving models can be implemented. This research was conducted at SMPN 1 Kateman to examine the effect of PhET simulation integrated with a problem-solving model on students’ conceptual understanding. The study employed an experimental design with a quasi-experimental, nonequivalent posttest-only control group. Data were collected using a conceptual understanding test consisting of 33 reasoned multiple-choice questions and analyzed using descriptive and inferential statistics. The results indicated that students in the experimental class outperformed those in the control class, demonstrating a significant improvement in conceptual understanding through the PhET simulation with a problem-solving model.